Preparation method of quartz crucible

By coating the glass -based high -pure quartz sand on the prefabricated part of quartz 坩埚 通过 通过, the problem of the unremarkable problem of the transparent layer of the air liquid wrap is solved, the number of bubbles and the amount of inner sand is reduced, and the quartz pupae are increased. Quality and reduction of costs.

CN119349864AActive Publication Date: 2025-01-24ANHUI ESTONE MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411264995.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

During the preparation process of existing quartz crucibles, the gas-liquid inclusions in the transparent layer cannot be completely removed, resulting in an increase in the number of bubbles in the crucible, affecting the crystallization of silicon and the quality of single crystal silicon. At the same time, the amount of high-purity inner layer is used for more sand. Increased costs.

Method used

The prefabrication of the premium preparation is used, and then the glass state high pure quartz sand is coated through the inner surface of the gas melting method, forming a transparent layer, reducing the amount of inner sand, and reducing the number of bubbles.

Benefits of technology

Effectively reduce the number of bubbles in the transparent layer, improve the quality and service life of quartz pupa, and at the same time reduce the amount of inner sand and reduce the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349864A_ABST
    Figure CN119349864A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a quartz crucible, and relates to the technical field of quartz crucibles, since a quartz crucible prefabricated part is prepared firstly and then a transparent layer is coated by gas refining, interface mixing of high-purity inner-layer sand and low-purity middle-layer sand or outer-layer sand is avoided, the interface is clearer, and the use amount of the inner-layer sand is reduced; the glassy-state high-purity quartz sand is firstly softened and then molten, so that when the synthesized glassy-state high-purity quartz sand is adopted as the inner-layer sand, the preparation method of the quartz crucible provided by the invention avoids the coating of the inner-layer sand on the middle-layer sand, reduces bubbles in the transparent layer of the quartz crucible, and improves the quality of the quartz crucible. Therefore, the adverse effect of bubbles on the use effect and the service life of the quartz crucible is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz crucibles, and in particular to a method for preparing a quartz crucible. Background Art

[0002] Quartz crucible is a sub-product of quartz products, with properties such as cleanliness, homogeneity, and high temperature resistance. From the perspective of physical thermal properties, the deformation point of quartz crucible is around 1100℃, the softening point is 1730℃, the maximum continuous use temperature is 1100℃, and it can be 1450℃ in a short time. It is currently widely used in the production process of refining crystalline silicon in the fields of solar energy and semiconductors, and is a consumable in the production process of crystalline silicon.

[0003] Early quartz crucibles were fully transparent. This transparent structure easily led to uneven heat transfer conditions, increasing the difficulty of growing crystal rods. In addition, the uniform structure required a large amount of high-quality, high-purity quartz sand and was costly. Therefore, this method of preparing quartz crucibles has been basically eliminated.

[0004] At present, quartz crucibles are generally produced by the electric arc method. The principle is: high-purity quartz powder of different purities is loaded step by step into a rotating molding mold with arbitrary tilting angles, and formed by centrifugal force (the conventional ratio is inner sand: middle sand: outer sand at a ratio of 3:4:3). The rotating device that has become a crucible is moved to the electrode rod, and then the electrode is powered to start the arc, and the vacuum system is started at the same time, so that it quickly melts into molten quartz in the shape of a crucible, and then taken out after cooling, and the melting of a quartz crucible is completed.

[0005] The quartz crucible prepared by the arc method is translucent and has an inner and outer layer structure. The outer layer is a region with high bubble density, called a bubble composite layer (corresponding to the outer layer sand and / or middle layer sand of low purity). The bubble composite layer is heated more evenly and has a better insulation effect; the inner layer is a 3-5mm region with low bubble density, called a transparent layer (prepared with high-purity inner layer sand). During the use of the crucible, the inner surface in contact with the silicon liquid is continuously melted into the silicon liquid, and the microbubbles in the transparent layer continue to grow. The bubbles near the innermost surface (referring to the part of the transparent layer closest to the inner surface 1-2mm) burst, and the silicon liquid releases quartz microparticles and microbubbles. These impurities will flow throughout the entire silicon melt in the form of microparticles and microbubbles along with the silicon liquid, directly affecting the crystallization of silicon (intact rod rate, crystallization rate, heating time, direct processing cost, etc.) and the quality of single crystal silicon (perforated sheets, black chips, etc.). Therefore, how to reduce the gas-liquid inclusions in high-purity natural quartz sand used for the transparent layer becomes the key to improving the quality of quartz crucibles, but the gas-liquid inclusions in natural quartz sand cannot be completely removed by existing technology.

[0006] In order to solve the problem that the gas-liquid inclusions in natural quartz sand cannot be completely removed, technicians used a synthetic method to prepare glassy high-purity quartz sand. However, when glassy high-purity quartz sand was used to replace part of the natural quartz sand as the inner layer sand, it was found that because the glassy high-purity quartz sand was amorphous and had a low softening temperature, it was wrapped around the natural quartz sand (crystallization). The gas-liquid inclusions in the natural quartz sand could not be removed, resulting in an increase in the number and size of bubbles in the quartz crucible, which limited the application of glassy high-purity quartz sand in quartz crucibles.

[0007] On the other hand, since the high-purity inner layer sand is mixed with the low-purity middle layer sand or outer layer sand at the interface during the mold forming process, a large amount of high-purity inner layer sand is used, resulting in increased costs. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a method for preparing a quartz crucible, which not only reduces the amount of inner sand used, but also reduces the number of bubbles in the transparent layer when glassy synthetic quartz sand is used as the inner sand.

[0009] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0010] The present invention provides a method for preparing a quartz crucible, comprising the following steps:

[0011] S1, pouring the outer layer sand into a rotating mold, and using a forming rod to melt and shape it to form the outer layer of the crucible;

[0012] S2, pouring the middle layer sand into the rotating mold on which the outer layer of the crucible has been formed, and melting and forming it using a forming rod to form the middle layer of the crucible;

[0013] S3, placing the rotating mold on which the outer layer and the middle layer of the crucible have been formed in a melting area, melting by a vacuum arc method, and demolding to obtain a quartz crucible preform;

[0014] S4, adding inner layer sand to the quartz crucible preform, using a gas refining melting method, rotating the quartz crucible preform, so that the molten inner layer sand is coated on the inner surface of the quartz crucible preform to form a transparent layer, and obtaining a quartz crucible.

[0015] Further, the outer layer of sand is at least one of natural quartz sand and synthetic quartz sand with a purity greater than 99.9%. Preferably, the outer layer of sand is natural quartz sand with a purity greater than 99.9%. The price of natural quartz sand is relatively low.

[0016] Further, the middle layer of sand is at least one of natural quartz sand and synthetic quartz sand with a purity greater than 99.99%. Preferably, the middle layer of sand is natural quartz sand with a purity greater than 99.99%. The outer layer of sand and the middle layer of sand are preferably natural quartz sand, which can reduce the preparation cost of the quartz crucible.

[0017] Furthermore, the inner layer of sand is at least one of natural quartz sand and synthetic quartz sand with a purity greater than 99.998%. Preferably, the inner layer of sand is synthetic quartz sand with a purity greater than 99.998%. Synthetic quartz sand has high purity and no gas-liquid inclusions, and the prepared crucible has few bubbles in the transparent layer.

[0018] Furthermore, the synthetic quartz sand includes at least one of glassy high-purity quartz sand and crystalline high-purity quartz sand. Preferably, the synthetic quartz sand is glassy high-purity quartz sand. Compared with the crystalline state, the glassy state has a low melting point, is easy to melt in the process of preparing the crucible, and is easy to process and shape.

[0019] Furthermore, the particle size of the outer layer sand, the middle layer sand and the inner layer sand ranges from 50 to 140 meshes. The appropriate particle size or different particle sizes can be selected and used in combination according to the needs.

[0020] Furthermore, the vacuum pressure of the melting in step S3 can reach a limit pressure value of -0.099 MPa.

[0021] Furthermore, the gases used in the gas refining and melting method in step S4 are hydrogen and oxygen.

[0022] Furthermore, in order to prevent the quartz crucible preform from cracking during the gas refining and coating process, the quartz crucible preform is preheated at a temperature of 500-900° C. before adding the inner layer of sand in step S4.

[0023] Furthermore, the flame of the gas refining and melting in step S4 should move with the molten inner layer sand to ensure that the inner layer sand is evenly coated on the inner surface of the quartz crucible preform without damaging the quartz crucible preform; on the other hand, the gas refining and melting method will increase the hydroxyl content in the quartz sand, reduce the viscosity of the quartz, and help improve fluidity and facilitate coating. These two technical effects are difficult to achieve by the arc method.

[0024] The present invention also provides a method for preparing glassy high-purity quartz sand, comprising the following steps:

[0025] (1) adding water to nano-scale amorphous silicon dioxide to prepare a slurry, and spray-drying the slurry to obtain nano-silicon dioxide agglomerates;

[0026] (2) subjecting the nano-silicon dioxide aggregates prepared in step (1) to mechanical static pressing to obtain bulk silicon dioxide;

[0027] (3) crushing, calcining and cooling the bulk silicon dioxide prepared in step (2) to obtain glassy high-purity quartz sand.

[0028] Furthermore, the average particle size of the nano-scale amorphous silicon dioxide is 5 to 100 nm. Amorphous silicon dioxide is a non-crystalline silicon dioxide. The present invention uses nano-scale amorphous silicon dioxide as a raw material to prepare glassy high-purity quartz sand. High-purity quartz sand in nature is crystalline, while the high-purity quartz sand prepared by the present invention is glassy, ​​which is a type of amorphous, and the processing temperature is relatively low.

[0029] Furthermore, the solid content of the slurry is 5 to 50%. In the present invention, if the solid content is lower than the range, the powder obtained by spray drying has more fine particles and poor fluidity; if the solid content is higher than the range, the viscosity of the slurry is high and the nozzle is easily blocked.

[0030] Furthermore, the air inlet temperature of the spray drying is 280-350° C., and the air outlet temperature is 80-120° C. In the present invention, the nano-scale amorphous silicon dioxide is transformed into nano-silicon dioxide agglomerates by spray drying.

[0031] Furthermore, the average particle size of the nano-silicon dioxide agglomerates is 100 to 500 μm. If the particle size is too large, the uniformity will be poor; if the particle size is too small, it will be difficult to prepare. Of course, the particle size of the nano-silicon dioxide agglomerates is also affected by the particle size of the raw material nano-scale amorphous silicon dioxide.

[0032] Furthermore, the pressure of the mechanical static pressure is 150-250 MPa, and the time is 10-40 min. Since the nano-silicon dioxide powder is very fluffy, if pressure is directly applied to the powder, it will expand again and become loose when the pressure is released, so it is necessary to add water to make a slurry first, and then make large particles by spray drying. In the present invention, the role of mechanical static pressure is to overcome the repulsive force between the nano-silicon dioxide particles, so that the distance between the nano-silicon dioxide particles is closer, so that the product obtained after sintering has less pores.

[0033] Furthermore, the average particle size of the blocky silicon dioxide after mechanical crushing is 50 to 400 μm.

[0034] Furthermore, the calcination temperature is 1000-1600°C and the time is 3-8h. The crushed blocky silicon dioxide is densified by calcination. If the calcination temperature is too high or the calcination time is too long, crystallization will occur and the energy consumption will be high; if the calcination temperature is too low or the calcination time is too short, it cannot be completely melted and the obtained product has a porous structure. Preferably, the calcination temperature is 1100-1200°C and the time is 5-6h.

[0035] The beneficial effects of the present invention are:

[0036] 1. Since the present invention first prepares the quartz crucible preform and then gas-refines and coats the transparent layer, the interface mixing of the high-purity inner sand and the low-purity middle sand or outer sand is avoided, the interface is clearer and the amount of the inner sand is reduced.

[0037] 2. Since the glassy high-purity quartz sand is first softened and then melted, when the present invention uses synthetic glassy high-purity quartz sand as the inner layer sand, the quartz crucible preparation method provided by the present invention avoids the inner layer sand from covering the middle layer sand, reduces the bubbles in the transparent layer of the quartz crucible, and thus solves the adverse effects of the existence of bubbles on the use effect and service life of the quartz crucible. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram of the structure of the quartz crucible after gas refining and melting in Example 2;

[0039] Figure 2 It is a schematic diagram of the structure of each layer in the quartz crucible before arc melting in Comparative Example 1;

[0040] Figure 3 for Figure 2 Schematic diagram of the structure of each layer of quartz sand after arc melting;

[0041] Figure 4 This is a cross-sectional view of the quartz crucible obtained in Example 1;

[0042] Figure 5 This is a cross-sectional view of the quartz crucible obtained in Comparative Example 2. DETAILED DESCRIPTION

[0043] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0044] The middle layer sand was purchased from Jiangsu Pacific Quartz Co., Ltd. with the model number of PQSF;

[0045] The outer layer of sand was purchased from Jiangsu Pacific Quartz Co., Ltd., quartz sand model PQSX1.

[0046] Example 1

[0047] Preparation of quartz crucible:

[0048] S1. Pour the outer layer of sand (80-130 mesh) into the rotating mold, rotate the mold 45-56 degrees, rotate at 65-70 rpm, and use a molding rod to melt and shape.

[0049] S2. Pour the middle layer of sand (60-120 mesh) into the rotating mold on which the outer layer of the crucible has been formed. Rotate the mold 45-56 degrees, rotate the speed 65-70 rpm, and use a forming rod to melt and form.

[0050] S3. Place the rotating mold with the outer layer and the middle layer of the crucible formed in the melting area, melt for 10 minutes using a vacuum arc method, with a vacuum pressure of -0.099 MPa and an arc power of 10 kW, cool naturally, and demold to obtain a quartz crucible preform.

[0051] S4. Preheat the quartz crucible preform to 500° C., then add inner layer sand (50-100 mesh, natural quartz sand, Unimin Corporation, USA, model ITOA-6) into the quartz crucible preform, and melt it by hydrogen / oxygen gas refining.

[0052] S5. Rotate the quartz crucible preform to coat the molten inner layer sand on the inner surface of the quartz crucible preform to form a transparent layer, thereby obtaining a quartz crucible.

[0053] Among them, the mass ratio of outer layer sand, middle layer sand and inner layer sand is 3:4:3.

[0054] Example 2

[0055] The preparation method of the quartz crucible in Example 2 is the same as that in Example 1, except that the inner layer of sand is vitreous high-purity quartz sand.

[0056] Preparation of glassy high-purity quartz sand: add amorphous silicon dioxide with a D50 particle size of 25 nm into water to prepare a slurry with a solid content of 20%; spray dry the slurry to obtain nano-silicon dioxide agglomerates with a D50 particle size of 300 μm; perform mechanical static pressing (pressure of 250 MPa, time of 0.5 h) on the nano-silicon dioxide agglomerates to obtain block silicon dioxide; mechanically crush the block silicon dioxide into particles of 40 to 85 mesh, calcine at 1200° C. for 5 h, and cool naturally to obtain glassy high-purity quartz sand of 50 to 100 mesh.

[0057] like Figure 1 As shown, the quartz crucible obtained in Example 2 is composed of a transparent layer and a bubble layer from the inside to the outside, and no transition layer is formed.

[0058] Example 3

[0059] The preparation method of the quartz crucible in Example 3 is the same as that in Example 1, except that the inner layer of sand is made of crystalline high-purity quartz sand synthesized according to Example 5 in patent CN202310980924.1.

[0060] Amorphous silica (particle size 5nm, specific surface area 200m 2 / g) 3kg, dried at 100℃ for 2h, 30g coupling agent (CH3O)3Si(CH2) 10CH3 is mixed with 100g of ethanol to obtain a modified liquid, and the modified liquid is mixed evenly with the dried amorphous silicon dioxide, dried (100°C, 2h), calcined at 1170°C for 10h, cooled naturally, and dispersed with air flow to obtain high-purity cristobalite with an average particle size of 180μm (about 80 mesh).

[0061] Comparative Example 1

[0062] The preparation method of the quartz crucible in Comparative Example 1 is the same as that in Example 1, except that no gas refining and melting are performed. Instead, the outer layer sand, the middle layer sand, and the inner layer sand are poured into a rotating mold in sequence, melted and formed using a forming rod, and then melted by a vacuum arc method.

[0063] like Figure 2 As shown, a mixed layer is formed between the inner sand and the middle sand before arc melting, and the mixed layer contains both the inner sand and the middle sand.

[0064] like Figure 3 As shown, the quartz crucible obtained after arc melting consists of a transparent layer, a transition layer and a bubble layer from the inside to the outside.

[0065] Comparative Example 2

[0066] The preparation method of the quartz crucible and the vitreous high-purity quartz sand in Comparative Example 2 is the same as that in Example 1, except that the nano-silicon dioxide agglomerates are not subjected to mechanical static pressure when preparing the vitreous high-purity quartz sand.

[0067] Preparation of glassy high-purity quartz sand: Amorphous silicon dioxide with a D50 particle size of 25 nm is added to water to prepare a slurry with a solid content of 20%; the slurry is spray-dried to obtain nano-silicon dioxide agglomerates with a D50 particle size of 300 μm; the nano-silicon dioxide agglomerates are calcined at 1200° C. for 5 h, and naturally cooled to obtain glassy high-purity quartz sand (opaque) of 50 to 100 mesh.

[0068] Comparative Example 3

[0069] The preparation method of the quartz crucible and the glassy high-purity quartz sand in Comparative Example 3 is the same as that in Example 1, except that the mechanical static pressure is too small when preparing the glassy high-purity quartz sand.

[0070] Preparation of glassy high-purity quartz sand: add amorphous silicon dioxide with a D50 particle size of 25 nm into water to prepare a slurry with a solid content of 20%; spray dry the slurry to obtain nano-silicon dioxide agglomerates with a D50 particle size of 300 μm; mechanically statically press the nano-silicon dioxide agglomerates (pressure of 5 MPa, time of 1 h) to obtain block silicon dioxide; mechanically crush the block silicon dioxide into particles of 40 to 85 mesh, calcine at 1200° C. for 5 h, and cool naturally to obtain glassy high-purity quartz sand (opaque) of 50 to 100 mesh.

[0071] Comparative Example 4

[0072] The preparation method of the quartz crucible and the vitreous high-purity quartz sand in Comparative Example 4 is the same as that in Example 1, except that the calcination temperature is too low when preparing the vitreous high-purity quartz sand.

[0073] Preparation of glassy high-purity quartz sand: add amorphous silicon dioxide with a D50 particle size of 25 nm into water to prepare a slurry with a solid content of 20%; spray dry the slurry to obtain nano-silicon dioxide agglomerates with a D50 particle size of 300 μm; perform mechanical static pressing (pressure of 250 MPa, time of 0.5 h) on the nano-silicon dioxide agglomerates to obtain block silicon dioxide; mechanically crush the block silicon dioxide into particles of 40 to 85 mesh, calcine at 900° C. for 6 h, and cool naturally to obtain glassy high-purity quartz sand (opaque) of 50 to 100 mesh.

[0074] The quartz crucibles prepared in the above examples and comparative examples were tested for transparent layer thickness and bubble quantity according to JC-T 1048-2007 "Quartz Crucible for Single Crystal Silicon Growth"; the hydroxyl content of the transparent layer was tested by infrared spectroscopy, and the results are shown in Table 1.

[0075] Table 1

[0076]

[0077] As can be seen from Table 1, in Example 2 and Example 3, synthetic glassy high-purity quartz sand and high-purity cristobalite are used as inner layer sand respectively, and no bubbles exist in the transparent layer of the quartz crucible prepared by the arc method + gas refining and melting method.

[0078] The quartz crucible of Example 1 uses high-purity natural quartz sand as the inner layer sand, but because it contains gas-liquid inclusions, the transparent layer contains a certain amount of bubbles (such as Figure 4 shown).

[0079] The quartz crucible of Comparative Example 1 is prepared by melting the outer layer sand, the middle layer sand and the inner layer sand by a conventional arc method after they are all formed. Due to the mixing at the interface between the middle layer sand and the inner layer sand, a transition layer is formed, resulting in a reduction in the thickness of the transparent layer.

[0080] In Example 1-3, the outer layer sand and the middle layer sand are first melted and formed by an arc method, and then the inner layer sand is melted by gas refining. The middle layer sand and the inner layer sand are not mixed at the interface, so the interface is clear. Under the condition of the same amount of inner layer sand, the transparent layer thickness of the produced quartz crucible is large.

[0081] The glassy high-purity quartz sand prepared under the corresponding process conditions in Comparative Example 2-5 has more pores, and the obtained glassy high-purity quartz sand is not transparent. It is impossible to obtain a transparent layer (such as Figure 5 shown).

[0082] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a quartz crucible, characterized in that: The steps include: S1, pouring the outer layer sand into a rotating mold, and using a forming rod to melt and shape it to form the outer layer of the crucible; S2, pouring the middle layer sand into the rotating mold on which the outer layer of the crucible has been formed, and melting and forming it using a forming rod to form the middle layer of the crucible; S3, placing the rotating mold on which the outer layer and the middle layer of the crucible have been formed in a melting area, melting by a vacuum arc method, and demolding to obtain a quartz crucible preform; S4, adding inner layer sand to the quartz crucible preform, using a gas refining melting method, rotating the quartz crucible preform, so that the molten inner layer sand is coated on the inner surface of the quartz crucible preform to form a transparent layer, and obtaining a quartz crucible.

2. The method for preparing a quartz crucible according to claim 1, characterized in that: The outer layer of sand is at least one of natural quartz sand and synthetic quartz sand with a purity greater than 99.9%; preferably, the outer layer of sand is natural quartz sand with a purity greater than 99.9%; The middle layer of sand is at least one of natural quartz sand and synthetic quartz sand with a purity greater than 99.99%; preferably, the middle layer of sand is natural quartz sand with a purity greater than 99.99%; The inner layer of sand is at least one of natural quartz sand and synthetic quartz sand with a purity greater than 99.998%; preferably, the inner layer of sand is synthetic quartz sand with a purity greater than 99.998%.

3. The method for preparing a quartz crucible according to claim 2, characterized in that: The synthetic quartz sand includes at least one of glassy high-purity quartz sand and crystalline high-purity quartz sand; preferably, the synthetic quartz sand is glassy high-purity quartz sand.

4. The method for preparing a quartz crucible according to claim 1, characterized in that: The particle sizes of the outer layer sand, the middle layer sand and the inner layer sand range from 50 to 140 meshes.

5. The method for preparing a quartz crucible according to claim 1, characterized in that: The vacuum pressure of the melting in step S3 reaches the ultimate pressure value of -0.099 MPa.

6. The method for preparing a quartz crucible according to claim 1, characterized in that: The gases used in the gas refining and melting method in step S4 are hydrogen and oxygen; Preferably, in step S4, the quartz crucible preform is preheated before adding the inner layer of sand, and the preheating temperature is 500-900° C.; Preferably, in step S4, the flame of the gas refining and melting moves along with the molten inner layer sand.

7. The method for preparing a quartz crucible according to claim 3, characterized in that: The preparation method of the glassy high-purity quartz sand comprises the following steps: (1) adding water to nano-scale amorphous silicon dioxide to prepare a slurry, and spray-drying the slurry to obtain nano-silicon dioxide agglomerates; (2) subjecting the nano-silicon dioxide aggregates prepared in step (1) to mechanical static pressing to obtain bulk silicon dioxide; (3) crushing, calcining and cooling the bulk silicon dioxide prepared in step (2) to obtain glassy high-purity quartz sand.

8. The method for preparing a quartz crucible according to claim 7, characterized in that: The average particle size of the nano-scale amorphous silicon dioxide is 5 to 100 nm; Preferably, the solid content of the slurry is 5-50%. Preferably, the inlet air temperature of the spray drying is 280-350°C, and the outlet air temperature is 80-120°C.

9. The method for preparing a quartz crucible according to claim 7, characterized in that: The average particle size of the nano-silicon dioxide agglomerates is 100 to 500 μm; Preferably, the mechanical static pressure has a pressure of 150 to 250 MPa and a time of 10 to 40 min; Preferably, the average particle size of the blocky silicon dioxide after mechanical crushing is 50 to 400 μm.

10. The method for preparing a quartz crucible according to claim 7, characterized in that: The calcination temperature is 1000-1600°C and the time is 3-8h; Preferably, the calcination temperature is 1100-1200° C. and the calcination time is 5-6 hours.

Citation Information

Patent Citations

  • Preparation method of high-purity cristobalite

    CN116873943A

  • Method for producing quartz crucible from composite quartz sands, and novel quartz crucible

    CN108059325A

  • High-purity quartz crucible for monocrystals and preparation method thereof

    CN108977879A

  • Quartz crucible preparation process, quartz crucible and crystal pulling method

    CN118164666A

  • Quartz crucible and single crystal thermal field

    CN216998661U